Narrative Rehabilitation: Manifestation of Chinese and Western Reform Ideals and Practices - Zhang, Xiaoye (International journal of offender therapy and comparative criminology, 2021)
The existing literature has shown that in Western penal systems there is often an official demand for narrative rehabilitation during treatment programs, and has criticized the requirement for a narrative change to correspond with the “judicial-correctional truth.” This study is based on participant observation in a male prison in mainland China. Through a comparative lens, this paper found that offenders in Western treatment programs are required to demonstrate a change in narrative identity that is immersed in details from their personal history and from judicial discourse, whereas the Chinese penal system scrutinizes individuality less and focuses more on adherence to a unified narrative form and structure. While both systems are concerned with social control and the legitimation of penal power, Chinese prisons are less concerned with cognitive specifics and more with overt behavioral compliance. Both practices of narrative rehabilitation may be insufficient in facilitating the complex needs of offenders to desist from reoffending.